Answer: The first 6 terms are = 8, 10, 12,14,16,18
Step-by-step explanation:
The NTH term of an Arithmetic Sequence is given as
an = a1 + (n - 1 ) d
where a1 = First term given as 8 and
d= common difference given as 2
Therefore We have that
the first term
an = a1 + (n - 1 ) d = 8+(1-1) 2
a1= 8
second term=
an = a1 + (n - 1 ) d= a2= 8 + (2-1) 2
= 8+ 2(1) = 10
3rd term
an = a1 + (n - 1 ) d= a3= 8 + (3-1) 2
= 8+ 2(2)= 8 + 4=12
4th term
an = a1 + (n - 1 ) d= a4= 8 + (4-1) 2
= 8+ 2(3)= 8+6=14
5th term
an = a1 + (n - 1 ) d= a5= 8 + (5-1) 2
= 8+ 2(4)=8+ 8=16
6th term
an = a1 + (n - 1 ) d= a6= 8 + (6-1) 2
= 8+ 2(5)=8 +10 =18
Answer:
tttt5556689
Step-by-step explanation:
hehe
Answer:
3200
Step-by-step explanation:
Given that:
The initial population of birds
= 100
The time duration t = 5 years
Growth rate (r) = (Birth - Death) rate
= 2 - 1
= 1 / year
∴
using the discrete-time form:
![N_t = N_o (1 + r )^t](https://tex.z-dn.net/?f=N_t%20%3D%20N_o%20%281%20%2B%20r%20%29%5Et)
![N_t = 100 (1 + 1 )^5](https://tex.z-dn.net/?f=N_t%20%3D%20100%20%281%20%2B%201%20%29%5E5)
![N_t = 100 (2 )^5](https://tex.z-dn.net/?f=N_t%20%3D%20100%20%282%20%29%5E5)
![N_t = 100 \times 32](https://tex.z-dn.net/?f=N_t%20%3D%20100%20%5Ctimes%2032)
![N_t = 3200](https://tex.z-dn.net/?f=N_t%20%3D%203200)
The question requires stating the Null and Alternative hypothesis for the scenario described :
Answer:
H0 : μ = 24
H1 : μ < 24
Step-by-step explanation:
The claim or hypothesis to be tested in a statistical problem or analysis is the alternative hypothesis. This is usually the opposite of the Null hypothesis which is the usually the initial truth until there is significant evidence provided using statistical test to prove otherwise.
The null hypothesis, H0 in the scenario above is :
H0 : μ = 24 ( average battery life is 24 hours)
The alternative hypothesis is the claim, that is. The mean battery life not up to 24 hours ;
H1 : μ < 24
Answer:
2 1/6
Step-by-step explanation:
Because the denominators are different, and there are whole numbers involved, then first make the fractions improper.
4 1/2 -> 9/2
6 2/3 -> 20/3
Next, make the denominators the same by multiplying each fraction by the denominator of the other.
9/2 * 3 = 27/6
20/3 * 2 = 40/6
Then you can subtract the numerators because the denominators are the same:
40/6-27/6= 13/6
Then you can convert to a mixed fraction if need be.